Differential induction of FosB isoforms throughout the brain by fluoxetine and chronic stress. (December 2015) - Vialou, Vincent; Thibault, Mackenzie; Kaska, Sophia; Cooper, Sarah; Gajewski, Paula; Eagle, Andrew; Mazei-Robison, Michelle; Nestler, Eric J.; Robison, A.J.
Abstract: Major depressive disorder is thought to arise in part from dysfunction of the brain's "reward circuitry", consisting of the mesolimbic dopamine system and the glutamatergic and neuromodulatory inputs onto this system. Both chronic stress and antidepressant treatment regulate gene transcription in many of the brain regions that make up these circuits, but the exact nature of the transcription factors and target genes involved in these processes remain unclear. Here, we demonstrate induction of the FosB family of transcription factors in ∼25 distinct regions of adult mouse brain, including many parts of the reward circuitry, by chronic exposure to the antidepressant fluoxetine. We further uncover specific patterns of FosB gene product expression (i.e., differential expression of full-length FosB, ΔFosB, and Δ2ΔFosB) in brain regions associated with depression – the nucleus accumbens (NAc), prefrontal cortex (PFC), and hippocampus – in response to chronic fluoxetine treatment, and contrast these patterns with differential induction of FosB isoforms in the chronic social defeat stress model of depression with and without fluoxetine treatment. We find that chronic fluoxetine, in contrast to stress, causes induction of the unstable full-length FosB isoform in the NAc, PFC, and hippocampus even 24 h following the final injection, indicating that these brain regions may undergo chronic activation when fluoxetine is on board, even in the absence of stress. We also find that only the stable ΔFosB isoform correlates with behavioral responses to stress. These data suggest that NAc, PFC, and hippocampus may present useful targets for directed intervention in mood disorders (ie, brain stimulation or gene therapy), and that determining the gene targets of FosB-mediated transcription in these brain regions in response to fluoxetine may yield novel inroads for pharmaceutical intervention in depressive disorders. Highlights: Fluoxetine induces FosB gene products in ∼25 distinct regions of adult mouse brain. Patterns of FosB gene products induced by fluoxetine differ by brain region. FosB gene product induction by fluoxetine differs from induction by stress. Only ΔFosB levels in PFC and nucleus accumbens correlate with behavioral response to stress.